Analisis Biaya dan Produksi Simplisia Temulawak (Curcumae rhizoma) di Desa Semagung Kecamatan Bagelen Kabupaten Purworejo - Nur Hidayah; Isna Windani; Uswatun Hasanah (Universitas Muhammadiyah Purworejo, 2019)
This study aims to determine: 1) a. Curcumae rhizoma cultivation techniques in the village of Semagung Bagelen District Purworejo Regency, b. The process of making dried ginger (simplicia) in the village of Semagung Bagelen District Purworejo Regency, 2) production costs, revenue, income, and profits on the production of dried ginger (simplicia) in the village of Semagung Bagelen District Purworejo Regency, 3) what factors influence in the production of dried ginger (simplisia) in the village of Semagung, Bagelen District, Purworejo Regency. This research method uses a descriptive method with a sample of 51 people. The results of the analysis note that 1) Curcumae rhizoma cultivation techniques in the village of Semagung include land management, planting, fertilizing, and harvesting. While the techniques for making simplicia include sorting, washing, weighing materials, chopping, drying, and packaging. 2) Revenue from Curcumae rhizoma simplicia in the amount of IDR 930,000 per planting season, income derived from the production of Curcumae rhizoma simplicia in the amount of IDR 630,117 and profits in the production of Curcumae rhizoma simplicia in the amount of IDR 103,128 per planting season. 3) Based on the F test results, the Fcount value is 78,887 and the F table is 1.29. A significant level also indicates 0,000 which is smaller than the error (α) which is 0.01. This means that Curcumae rhizoma production is influenced simultaneously by the independent variables in the model. T-Test results note that the independent variables that significantly influence the production of ginger are: rhizome and simplicia price.